RESEARCH OF ROBOTIC SYSTEMS CONTROL METHODS USING MOTION RECOGNITION TOOLS, MACHINE LEARNING AND SKELETALIZATION ALGORITHMS - Sakalys, Paulius; Savulioniene, Loreta; Savulionis, Dainius (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The aim of the research is to develop possible control methods of robotic systems based on the usability of motion detection equipment, skeletalization algorithms and robotic systems, integrating them into the existing test bench by performing compatibility tests. The article reviews the possible motion detection systems, establishing the criteria of applicability in the control of robotic systems, describes the experimental research plan, research stand, discusses the research results and presents summarized conclusions and suggestions for the integration of research results into the educational process.